Devil's Oak - Leoson, Mary Carroll (MT Open Press, Middle Tennessee State University, 2025)
Devil’s Oak: Waking the Feminine Wound is a short story collection that features strong female characters against a backdrop of ghosts, fairy tales, and urban legends. The thirteen stories subvert the historical narrative of women in fairy tales, positioning them as bold and willing to step into the face of danger. “The Braided Veil” features a young orphan in Victorian New Orleans who seeks revenge upon her mother’s abuser. “Devil’s Oak” addresses the horrors of slavery through the eyes of a young girl who learns that her family owned human beings. “Good Little Girls” takes readers back to childhood in which a sick girl explores her neighbor’s attic on a stormy day; she discovers more than she bargained for. “The Game” features relational aggression in the 1990’s in a “mean girls” style that takes a grizzly turn. “Selkie Skin” leans into Celtic lore, following a young pregnant girl who longs for freedom. “The Ripper Society” reaches back through time to Jack the Ripper’s wife, who discovers his misdeeds and takes matters into her own hands. “She Has Seen the Wolf” is longer story that connects to my novel, The Butterfly Circle; when a graduate student learns she is pregnant, she uncovers her family’s connected history to a haunted home for unwed mothers. In “Roots in the Cove,” a woman in an unhealthy relationship shapeshifts into a bear on a trip to Gatlinburg and finally finds her freedom. Both “Marsh Girl” and “Cicadas in the Suburbs” explore the psychological challenges of suburban life, including postpartum depression and the longing for the magic of youth. In “Honey Tree,” a divorced woman seeks comfort from the bees, and in “Crow Woman,” a widow faces metaphorical death and is reborn. Finally, “Ghost Apples” is a retelling of Snow White from the perspective of the queen; she shapeshifts into a wolf to protect a young girl who has been attacked and seeks revenge upon her abuser.